Biotin-tagged fluorescent sensor to visualize 'mobile' Zn2+ in cancer cells. Issue 69 (10th August 2018) - Fang, Le; Trigiante, Giuseppe; Kousseff, Christina J.; Crespo-Otero, Rachel; Philpott, Michael P.; Watkinson, Michael
Abstract : A biotin-tagged fluorescent sensor was developed to image Zn 2+ in cancer cells specifically, which showed no entry to normal cells. Abstract : A cancer cell-targeting fluorescent sensor has been developed to image mobile Zn 2+ by introducing a biotin group. It shows a highly selective response to Zn 2+ in vitro, no toxicity in cellulo and images 'mobile' Zn 2+ specifically in cancer cells. We believe this probe has the potential to help improve our understanding of the role of Zn 2+ in the processes of cancer initiation and development.